A Quantitative Assessment of the Accuracy and Reliability of Robotically Guided Percutaneous Pedicle Screw Placement: Technique and Application Accuracy. Issue 4 (6th February 2019) - Godzik, Jakub; Walker, Corey T; Hartman, Cory; de Andrada, Bernardo; Morgan, Clinton D; Mastorakos, George; Chang, Steven; Turner, Jay; Porter, Randall W; Snyder, Laura; Uribe, Juan
Abstract: BACKGROUND: Minimally invasive surgery (MIS) and anterior (ALIF), transforaminal (TLIF), or lateral lumbar interbody fusion (LLIF) often require percutaneous pedicle screw fixation (PSF) to achieve circumferential fusion. Robotic guidance technology may augment workflow to improve screw placement and decrease operative time. OBJECTIVE: To report surgical experience with robotically assisted percutaneous screw placement following LLIF. METHODS: Data from fusions with robotically assisted PSF in prone or lateral decubitus positions was reviewed. A CT-guided robotic guidance arm was used for screw placement (Excelsius GPS™, Globus Medical Inc, Audubon, Pennsylvania). Postoperative CT imaging facilitated screw localization. 3-dimensional and 2-dimensional coordinates of the screw tip and tail were calculated and compared with a target trajectory to calculate targeting errors. Breach was defined as a violation of the lateral or medial pedicle wall. RESULTS: Robotic-guided screw placement was successful in 28/31 patients. In those patients, 116/116 screws were successfully implanted. The breach rate was 3.4% (4/116). Across 17 patients (70 screws), mean 3-D accuracy was 5.0 ± 2.4 mm, mean 2-D accuracy was 2.6 ± 1.1 mm, and mean angular offset was 5.6 ± 4.3° with corresponding intraclass correlation coefficients (ICC) of 0.775 and 0.693. 3-dimensional accuracy correlated with age (R = 0.306, P  = .011) and BMI (R = 0.252, P  = .038). Accuracy did not significantly differ among vertebral body levels ( P  > .22). Mean operative time for MIS-TLIF and percutaneous screws was 277 ± 52 and 183 ± 54 min, respectively. Operative time did not significantly decrease across either group ( P  > .187). CONCLUSION: The Excelsius GPS™ robotic guidance system allows accurate PSF in most cases with 2 mm 2-D accuracy. Future studies are needed to demonstrate the utility of this novel guidance system and workflow improvement.